Cost-effectiveness of secukinumab compared to other biologics in the treatment of ankylosing spondylitis in Finland - Purmonen T; Puolakka K; Mishra D; Gunda P; Martikainen J (Dove Medical Press, 2019)
Timo Purmonen,1 Kari Puolakka,2 Dinesh Mishra,3 Praveen Gunda,3 Janne Martikainen4 1Novartis Finland Oy, Espoo, Finland; 2South Karelia Central Hospital, Lappeenranta, Finland; 3Novartis Product Lifecycle Services-NBS, Novartis Healthcare Private Limited, Hyderabad, India; 4School of Pharmacy, University of Eastern Finland, Kuopio, Finland Aim: This study assesses the cost-effectiveness of secukinumab vs currently licensed biologics for the treatment of ankylosing spondylitis (AS) from the Finnish health care system perspective. Methods: A semi-Markov model compared secukinumab with adalimumab, adalimumab biosimilar, certolizumab pegol, etanercept, etanercept biosimilar, golimumab, and infliximab in a biologic-naïve population over a lifetime horizon. The Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) was used to assess the treatment response. Efficacy inputs were obtained from the network meta-analysis, and other model inputs were obtained from the published literature and Finnish sources. Main study outcomes included quality-adjusted life years (QALYs) gained and incremental cost-effectiveness ratio in terms of cost per QALY gained. Robustness of results was confirmed by sensitivity analyses and alternative scenario analyses. Results: Secukinumab achieved highest QALYs (13.1) at lowest expected lifetime cost (€279,872) vs other comparators in biologic-naïve AS patients in the base case analysis, thus it dominated other biologics. Golimumab had a second highest QALYs (12.9) at the total cost of €309,551. Results were sensitive to variation in BASDAI 50 response for secukinumab, baseline Bath Ankylosing Spondylitis Functional Index (BASFI) score across all drugs, change in BASDAI and BASFI scores, and discount rates as observed in the one-way sensitivity analyses. Secukinumab was either dominant or cost-effective treatment in different alternative scenarios. Conclusion: Secukinumab presented itself to be the dominant (ie, less costly and more effective) treatment vs other comparators for the biologic-naïve patients with AS in Finland. Keywords: radiographic axial SpA, secukinumab, cost-effectiveness, Finland, economic evaluation, health economics, IL-17, anti-TNF